2017
DOI: 10.1002/ejp.1095
|View full text |Cite
|
Sign up to set email alerts
|

The association between sleep quality, low back pain and disability: A prospective study in routine practice

Abstract: In clinical practice, sleep quality, low back pain and disability are associated. However, sleep quality at baseline does not predict improvement in pain and disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
(82 reference statements)
2
16
1
2
Order By: Relevance
“…In our sample, 11% of participants with chronic LBP had concomitant insomnia, which was lower than the 55-59% reported in other studies [4][5][6]. This was expected as our insomnia definition required daytime impairment as in the DSM-5 criteria for insomnia, rather than the any symptoms of insomnia.…”
Section: Answer C) Is Presence Of Insomnia Associated With the Prevalence Of Chronic Lbp?contrasting
confidence: 52%
See 1 more Smart Citation
“…In our sample, 11% of participants with chronic LBP had concomitant insomnia, which was lower than the 55-59% reported in other studies [4][5][6]. This was expected as our insomnia definition required daytime impairment as in the DSM-5 criteria for insomnia, rather than the any symptoms of insomnia.…”
Section: Answer C) Is Presence Of Insomnia Associated With the Prevalence Of Chronic Lbp?contrasting
confidence: 52%
“…Chronic LBP is the top cause for years lived with disability in The Global Burden of Disease study 2013 [3]. Insomnia symptoms are highly prevalent in individuals with chronic LBP, with 55-59% of sufferers [4][5][6] reporting insomnia symptoms, such as poor sleep quality, non-restorative sleep, waking up too early, and difficulty initiating and maintaining sleep [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, research conducted in US military hospitals among 757 participants reported that sleep disorder is significantly associated with LBP-related health visits among the military population (Rhon et al, 2019). In addition, a cohort study conducted among adults reported improvement in LBP with increased sleep quality (Kovacs et al, 2018). However, there is a lack of research articles regarding the quantity and quality of sleep required to recover from strenuous military drills.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Spanish study sought to test it scientifically, investigating the association between sleep quality and low back pain in routine clinical practice. 1 A total of 461 patients with lower back pain were recruited from both primary and secondary care, and followed up after 3 months. Patients who had an improvement in sleep during the follow-up period also had improvements in lower back pain and disability.…”
Section: Sleep Quality Febrile Seizures Interpreters and Doulasmentioning
confidence: 99%